Etiopathogenic role of ERK5 signaling in sarcoma: prognostic and therapeutic implications - Adrián Sánchez-Fdez; Sofía Matilla-Almazán; Sofía Del Carmen; Mar Abad; Elena Arconada-Luque; Jaime Jiménez-Suárez; Luis Miguel Chinchilla-Tábora; Mª José Ruíz-Hidalgo; Ricardo Sánchez-Prieto; Atanasio Pandiella; Azucena Esparís-Ogando (Experimental and Molecular Medicine, 2023)
Abstract Sarcomas constitute a heterogeneous group of rare and difficult-to-treat tumors that can affect people of all ages, representing one of the most common forms of cancer in childhood and adolescence. Little is known about the molecular entities involved in sarcomagenesis. Therefore, the identification of processes that lead to the development of the disease may uncover novel therapeutic opportunities. Here, we show that the MEK5/ERK5 signaling pathway plays a critical role in the pathogenesis of sarcomas. By developing a mouse model engineered to express a constitutively active form of MEK5, we demonstrate that the exclusive activation of the MEK5/ERK5 pathway can promote sarcomagenesis. Histopathological analyses identified these tumors as undifferentiated pleomorphic sarcomas. Bioinformatic studies revealed that sarcomas are the tumors in which ERK5 is most frequently amplified and overexpressed. Moreover, analysis of the impact of ERK5 protein expression on overall survival in patients diagnosed with different sarcoma types in our local hospital showed a 5-fold decrease in median survival in patients with elevated ERK5 expression compared with those with low expression. Pharmacological and genetic studies revealed that targeting the MEK5/ERK5 pathway drastically affects the proliferation of human sarcoma cells and tumor growth. Interestingly, sarcoma cells with knockout of ERK5 or MEK5 were unable to form tumors when engrafted into mice. Taken together, our results reveal a role of the MEK5/ERK5 pathway in sarcomagenesis and open a new scenario to be considered in the treatment of patients with sarcoma in which the ERK5 pathway is pathophysiologically involved.